Penegakan Hukum terhadap Kekerasan Penganiayaan Mengakibatkan Matinya Orang: Studi di Pengadilan Negeri Sungguminasa - Sandi, Sandi (Sovereign: International Journal of Law, 2023)
This study aims to determine law enforcement and what factors influence law enforcement against perpetrators of violence that lead to the death of people. This research is included in the type of juridical empirical research, which is research that examines laws and regulations to answer existing problems by connecting facts or phenomena with violence that causes a person’s death. This research was conducted in the jurisdiction of the Sungguminasa District Court. The data collection techniques used in this research were literature study and interviews. The data analysis technique used is qualitative data analysis techniques. The results showed that law enforcement against violence that resulted in death in the community could not be minimized because the application of sanctions was considered light and the crime of violent maltreatment was increasing every year. Factors that influence law enforcement against violent persecution that results in death in the community are legal structure factors, legal culture factors and public awareness factors.